Effect of microbial interaction on flavor quality in Chinese baijiu fermentation - Gao, Lei; Zhou, Jian; He, Guiqiang (Frontiers in Nutrition, 2022)
Chinese baijiu brewing is an open, complex, and synergetic of functional microbiota fermentation process. Microbial interaction is pivotal for regulation of microbial structure and function in the brewing microecosystem, consequently affecting the flavor and quality of baijiu. This paper mainly summarizes the effect of microbial interactions among functional microbiota on the growth performance, flavor formation, and safe quality in baijiu fermentation process. In addtion, the review specifically emphasizes on the microbial interactions for regulation of “Ethyl Caproate-Increasing and Ethyl Lactate-Decreasing” in Chinese strong-flavor baijiu. Furthermore, construction of synthetic microbiota by metabolic characteristics of the functional microbes and their interactions for regulating and controlling flavor quality of Chinese baijiu is also reviewed and prospected.